Pengaruh Model Pembelajaran Kooperatif Tipe Make A Match Terhadap Motivasi dan Hasil Belajar Matematika pada Siswa Kelas VII SMP Yapis Timika - Rasul, A. (Mandalika Mathematics and Educations Journal, 2021)
The problem in learning mathematics at SMP Yapis Timika is that students' motivation and mathematics learning outcomes are low. Furthermore, the teacher never uses the cooperative learning model to make students less enthusiastic in learning. Therefore the aim of this study was to determine the effect of the make a match cooperative learning model on the motivation and learning outcomes of mathematics in class VIIA students of SMP Yapis Timika in academic year 2019/2020. This type of research is experimental research. The experimental design used was a quasi-experimental design with a posttest-only control design. The sampling technique used was purposive sampling where in class VII A was obtained (21 students) as the experimental class and VII BÃƒÂ‚Ã‚Â  (20- students) as the control class. Based on the results of data analysis, it was found that the average value of students' motivation to learn mathematics in the experimental class with a score of 61.03 in the good category, while the control class got an average score of 57.07 which was categorized quite good. And the experimental class student results data obtained an average score of 81.71 with a success rate of 80.64%. While the control class got an average score of 73.56 with a success rate of 53.33%. And the t test on student learning outcomes obtained tcount> ttable or 3.08> 2.01. The results of this study can be concluded, there is an effect of the make a match cooperative learning model on the motivation and learning outcomes of grade VII students of SMP Yapis Timika in academic year 2019/2020ÃƒÂ‚Ã‚Â AbstrakPermasalahan dalam pembelajaran matematika di SMP Yapis Timika bahwa motivasi siswa dan hasil belajar matematika siswa rendah. Lebih lanjut, guru tidak pernah menggunakan model pembelajaran kooperatif membuat siswa kurang antusias dalam belajar. Oleh karena itu tujuan dari penelitian ini adalah untuk mengetahui pengaruh model pembelajaran kooperatif tipe make a Match terhadap motivasi dan hasil belajar matematika pada siswa kelas VII SMP Yapis Timika tahun akademik 2019/2020. Jenis penelitian ini adalah kuasi eksperimen dengan desain kontrol posttest-only. Teknik pengambilan sampel yang digunakan adalah purposive sampling dimana kelas VII A (21 siswa) sebagai kelas eksperimen dan VIIB (20- siswa) sebagai kelas kontrol. Berdasarkan hasil analisis data didapatkan nilai rata-rata motivasi belajar matematika siswa kelas eksperimen dengan nilai 61,03 dengan kategori baik, sedangkan kelas kontrol mendapat nilai rata-rata 57,07 dengan kategori cukup baik. Kelas eksperimen didapatkan skor rata-rata 81,71 dengan angka keberhasilan 80,64%. Sedangkan mendapat skor rata-rata 73,56 dengan angka keberhasilan 53,33%. Dan uji t tentang hasil belajar siswa didapat thitung> ttabel atau 3,08> 2,01. Hasil penelitian menunjukkan ada pengaruh model pembelajaran kooperatif tipe make a Match terhadap motivasi dan hasil belajar siswa kelas VII SMP Yapis Timika tahun akademik 2019/2020ÃƒÂ‚Ã‚Â